Malaysian Muslim investors’ behaviour towards the blockchain-based Bitcoin cryptocurrency market - Ayedh A.; Echchabi A.; Battour M.; Omar M. (Emerald Group Publishing Ltd., 2024)
Purpose: This study aims to examine the factors that could increase the investment in the Bitcoin market among Malaysian Muslim communities. Design/methodology/approach: The study used a survey questionnaire to collect data for a sample of 200 Muslim respondents in Malaysia. Subsequently, the collected data was analysed using structural equation modelling, as well as basic descriptive statistics and one sample test. Findings: The findings showed that compatibility, awareness and facilitating conditions have a significant impact on Malaysian Muslim communities’ investment in the Bitcoin market. Originality/value: It is worth emphasizing that this is one of the earliest studies that examine the Muslim communities’ perception and willingness to invest in the Bitcoin market. Hence, it is expected to be one of the foundations for future studies in this area.